Contrast sensitivity is associated with outer‐retina thickness in early‐stage diabetic retinopathy. Issue 2 (13th September 2019) - McAnany, J. Jason; Park, Jason C.; Liu, Karen; Liu, Michelle; Chen, Yi‐Fan; Chau, Felix Y.; Lim, Jennifer I.
Abstract: Purpose: To determine the relationship between contrast sensitivity (CS) and outer‐retina thickness (ORT) in diabetics who have minimal or no diabetic retinopathy (DR). Methods: Twenty non‐diabetic control subjects and 40 type‐2 diabetic subjects participated (20 had no clinically apparent DR [NDR] and 20 had mild non‐proliferative DR [NPDR]). No subject had a history of treatment for macular oedema. Letter CS, microperimetry (MP) sensitivity and visual acuity (VA) were measured. Letter CS and MP measurements were performed over the central 6° of the visual field. Spectral domain optical coherence tomography (SD‐OCT) images were obtained at corresponding locations, outer‐retina thickness was quantified, and structure–function relationships were evaluated. Results: Analysis of variance indicated significant letter CS differences among the groups (p < 0.001). Letter CS was reduced significantly for the mild NPDR group (p < 0.001; 33% reduction), but not the NDR group (p = 0.08). There were no significant differences in MP sensitivity or ORT among the groups (both p > 0.10). Nevertheless, Hoeffding's D tests indicated significant associations between ORT and letter CS (p < 0.001) and between ORT and MP sensitivity for the mild NPDR group (p = 0.01). VA was not significantly associated with ORT for either diabetic group (both p > 0.49). Conclusions: Outer‐retina thickness is associated with letter CS and MP sensitivity, but not VA, in mild NPDR. This finding highlights the usefulness of simple letter CS measures and suggests neural dysfunction can occur in the absence of marked structural abnormalities in early‐stage DR.